An image-based method for quantification of masseter muscle deformation - Yang Yang; Foong, Kelvin Weng Chiong; Sim Heng Ong; Yagi, Masakazu; Takada, Kenji (2012 5th International Conference on Biomedical Engineering and Informatics, 2012)
Current methods that evaluate the functions of masseter muscles (MM) are not suited to fully describing their functional roles. The aim of this study was to develop a method to quantify the deformations of MM in simulated mandibular movements for individual study. A normal adult male subject underwent magnetic resonance (MR) scans of the head at four mandibular positions: mandibular rest (M0), maximum intercuspation (M1), medium jaw-opened (M2), and maximum jaw-opened (M3) positions. The muscle models of the subject were reconstructed from the four sets of MR images, and the deformations of the MM in the three cases, i.e., from M0 to M1, from M0 to M2 and from M2 to M3, were quantified in terms of the displacements of region correspondences between the muscle models before and after the mandibular position changed. The functional activities along the entire body and at specific anatomic compartments of the subject-specific MM were quantified and visualized using the quantified deformation fields. The directions of the active and positive muscle tensions during the simulated mandibular movements were indicated by the resultant directions of the deformations, respectively. The proposed method revealed the anatomic architectural and biomechanical characteristics of the subject-specific MM appropriately and meaningfully in the simulated mandibular movements.